Digital Transformation for the Retail Sector - Mansukhani, Puneet (Digital Repository of Theses, 2024)
Digital transformation in the retail sector represents a comprehensive overhaul of retail operations, leveraging digital technologies to optimize processes, enhance customer experience, and achieve competitive advantage. This transformation encompasses a wide range of technologies, including e-commerce platforms, mobile apps, artificial intelligence (AI), machine learning, big data analytics, and the Internet of Things (IoT), to create seamless omnichannel experiences that bridge the gap between online and physical shopping environments. The core objective of digital transformation in retail is to respond to changing consumer behaviors and expectations, which are increasingly oriented towards personalized, convenient, and immersive shopping experiences. By integrating digital technologies, retailers can gain insights into customer preferences and behaviors, enabling them to offer tailored recommendations, improve inventory management, and streamline supply chain operations. Furthermore, digital transformation facilitates the implementation of advanced customer service solutions, such as chatbots and virtual assistants, enhancing customer engagement and support. It also empowers retailers to implement innovative business models, such as subscription services, and explore new revenue streams through data monetization. However, the journey towards digital transformation is not without challenges. It requires significant investment in technology and skills, a culture shift towards innovation and agility, and a strategic approach to data security and privacy. Retailers must navigate these challenges carefully, ensuring that their digital transformation initiatives align with overall business goals and deliver tangible value to customers. In conclusion, digital transformation for the retail sector is not merely an option but a necessity in the digital age. It offers retailers the opportunity to innovate, differentiate, and thrive in a highly competitive and ever-evolving marketplace. Successful digital transformation in retail hinges on a holistic approach that encompasses technology, people, and processes, aimed at enhancing customer satisfaction and driving business growth.